2018
DOI: 10.3390/s18092755
|View full text |Cite
|
Sign up to set email alerts
|

Nanobiosensing Platforms for Real-Time and Non-Invasive Monitoring of Stem Cell Pluripotency and Differentiation

Abstract: Breakthroughs in the biomedical and regenerative therapy fields have led to the influential ability of stem cells to differentiate into specific types of cells that enable the replacement of injured tissues/organs in the human body. Non-destructive identification of stem cell differentiation is highly necessary to avoid losses of differentiated cells, because most of the techniques generally used as confirmation tools for the successful differentiation of stem cells can result in valuable cells becoming irreco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…To identify cell populations, conventional methods, such as immunochemical staining, fluorescence-activated cell sorting, qRT-PCR, and Western blotting, have been widely used to define and monitor cell differentiation status (11). However, most of these methods require destructive fixation or lysis steps and are generally time consuming (12), limiting their applications toward cell monitoring for clinical transplantation.…”
mentioning
confidence: 99%
“…To identify cell populations, conventional methods, such as immunochemical staining, fluorescence-activated cell sorting, qRT-PCR, and Western blotting, have been widely used to define and monitor cell differentiation status (11). However, most of these methods require destructive fixation or lysis steps and are generally time consuming (12), limiting their applications toward cell monitoring for clinical transplantation.…”
mentioning
confidence: 99%
“…During the development of drugs, stem cell differentiation is exceptionally favorable for obtaining specific cells of interest. These cells are further treated with drug candidates to confirm drug safety and efficacy [ 157 , 158 ]. Many recent studies have reported the non-destructive and label-free detection of stem cell pluripotency and differentiation via electrochemical biosensors to avoid irreversible cell damage after analysis [ 146 , 159 , 160 , 161 ].…”
Section: Electrochemical Biosensing For Highly Proliferative Cellsmentioning
confidence: 99%
“…Using this coating technology, which can pattern graphene oxide on a specific surface using moisture treatment with GO [ 110 , 111 , 112 ], it is possible to induce cells to preferentially adhere to the wall of the PDMS micro-well. They photographed micro-well monolayers via Raman spectroscopy to identify vertical graphene patterns coated on the wall [ 113 , 114 ]. Cells attached to the wall of the spherical micro-well begin to fill the wells time-dependently and eventually form a tumor cell spheroid inside the well.…”
Section: Controlling 3d Cancer Cell Microenvironments Using Graphementioning
confidence: 99%